2020
DOI: 10.1371/journal.pbio.3000762
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic centriolar localization of Polo and Centrobin in early mitosis primes centrosome asymmetry

Abstract: Centrosomes, the main microtubule organizing centers (MTOCs) of metazoan cells, contain an older "mother" and a younger "daughter" centriole. Stem cells either inherit the mother or daughter-centriole-containing centrosome, providing a possible mechanism for biased delivery of cell fate determinants. However, the mechanisms regulating centrosome asymmetry and biased centrosome segregation are unclear. Using 3D-structured illumination microscopy (3D-SIM) and live-cell imaging, we show in fly neural stem cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 52 publications
(141 reference statements)
3
19
0
1
Order By: Relevance
“…Multiple mechanisms contribute to creating the asymmetry between the mother and daughter centrosomes in Drosophila neuroblasts. The daughter centrosome's MTOC activity is upregulated by recruitment of Cnb and Polo, which occurs during mitosis in preparation for centrosome asymmetry in the next interphase [ 45 , 46 ]. In parallel, the mother centrosome's MTOC activity is downregulated, releasing it from the apical cortex, leading to its eventual inheritance by the differentiating cell.…”
Section: How Could Centrosome Asymmetry Contribute To Asymmetric Cellmentioning
confidence: 99%
“…Multiple mechanisms contribute to creating the asymmetry between the mother and daughter centrosomes in Drosophila neuroblasts. The daughter centrosome's MTOC activity is upregulated by recruitment of Cnb and Polo, which occurs during mitosis in preparation for centrosome asymmetry in the next interphase [ 45 , 46 ]. In parallel, the mother centrosome's MTOC activity is downregulated, releasing it from the apical cortex, leading to its eventual inheritance by the differentiating cell.…”
Section: How Could Centrosome Asymmetry Contribute To Asymmetric Cellmentioning
confidence: 99%
“…In polo mutants, Pon and Numb are not asymmetrically localized to basal cortex, causing a failure of asymmetric division that leads to neuroblast over-proliferation. Additionally, increased Polo activity at the daughter centrosomes relative to mother centrosomes is essential for the retention of the daughter centrosome in the neuroblast cell following cell division (Januschke et al, 2013 ; Conduit et al, 2014 ; Gallaud et al, 2020 ). The extent to which the resulting asymmetric inheritance of mother and daughter centrosomes regulates the fate of apical and basal daughter cells remains an open area of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, morphogenesis during embryonic Drosophila development has been studied using optogenetics in a variety of ways [ 90 ]. A non-exhaustive list of optogenetic approaches to study Drosophila development includes: the structure of centrosomes [ 91 ], Erk signalling [ 27 , 92 94 ], Toll signalling [ 95 ], adhesion [ 56 , 96 98 ], cell shapes [ 99 ], GTPase activity [ 45 , 100 110 ], anterior-to-posterior patterning through Bicoid [ 111 ], Wnt [ 112 ], and Notch signalling [ 113 ]. One approach that looked at phosphatidylinosital-4,5 biphosphate [PI(4,5)P2] during Drosophila ventral furrow formation showed that it was required for apical constriction, an essential tissue invagination process [ 114 , 115 ].…”
Section: Optogenetic Approachesmentioning
confidence: 99%